Unveiling the Impact of Firm-Level and Instrument-Level Risks on Corporate Sukuk Returns in Indonesia - Dian Yuni Anggraeni; Ravika Nabila Putri (Tazkia Islamic University College, 2026)
This study aims to examine and provide empirical evidence regarding the impact of sukuk risk and company risk on sukuk returns. The analysis focuses on companies listed on the Indonesia Stock Exchange (IDX) with outstanding sukuk instruments during the 2021–2023 period. Utilizing a quantitative approach, the study analyzed a sample of 15 publicly listed companies, resulting in 186 observations of outstanding sukuk. Multiple linear regression analysis was employed to test the relationship between the variables, with sukuk risk proxied by credit ratings and company risk measured by leverage ratios. The empirical results indicate that both sukuk risk and company risk exert a significant negative effect on sukuk returns. These findings imply that, holding other factors constant, sukuk returns tend to appreciate as risk levels—both at the instrument and corporate levels—decrease. This inverse relationship suggests that investors in the Indonesian sharia capital market prioritize capital security and creditworthiness, viewing high-risk profiles as a deterrent to return stability. This research contributes to the literature on Islamic finance by providing a granular understanding of risk-return dynamics during a volatile economic recovery period. Practically, it offers a framework for investors to make more informed and prudent investment decisions by evaluating the specific risks associated with sharia-compliant debt instruments.